2013
DOI: 10.1001/jamaoto.2013.4690
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Otopathogenic Biofilms by Organoselenium-Coated Tympanostomy Tubes

Abstract: The OSe coating is a potential long-lasting agent to prevent biofilm development on tympanostomy tubes by otopathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The microtiter plate culture assay was utilized to develop the biofilms as previously described [15,16]. Briefly, aliquots of overnight cultures of the tested strain in LB broth were harvested, washed in 1 mL PBS, and diluted in PBS to an OD 600 of 0.02.…”
Section: Biofilm Developmentmentioning
confidence: 99%
“…The microtiter plate culture assay was utilized to develop the biofilms as previously described [15,16]. Briefly, aliquots of overnight cultures of the tested strain in LB broth were harvested, washed in 1 mL PBS, and diluted in PBS to an OD 600 of 0.02.…”
Section: Biofilm Developmentmentioning
confidence: 99%
“…•-) in a continuous process in which Se donates an electron to oxygen and acquires one from sulfur compounds (such as glutathione) that are present in all body fluids [1]. Recently, it has been shown that organo-selenium can be attached to different biomaterials and medical devices to block the formation of P. aeruginosa and S. aureus biofilms on those materials [2][3][4][5][6]. Once a biofilm is formed on one of these devices, the only remedy is to replace the infected device, making prevention paramount.…”
Section: Introductionmentioning
confidence: 99%
“…Once a biofilm is formed on one of these devices, the only remedy is to replace the infected device, making prevention paramount. Selenium has additionally shown promise for this purpose in that unlike other antibacterial agents, longer periods of exposure to an aqueous environment do not compromise the effectiveness of the coating [2][3][4][5][6]. Biofilm formation occurring in a wound itself inhibits wound healing [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that organo-selenium can be covalently attached to many types of surfaces and still generate superoxide radicals (O 2 • ¯) as it has been shown in the past with different types of materials [ 17 , 18 , 19 , 20 , 21 ]. The di-selenide compounds, used in the synthesis of the coating, are reduced by thiols (sulfhydryl groups, R-SH) which can be found in physiological fluids, and form selenide anions, R-Se − [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that organo-selenium compounds could be covalently bound to solid matrixes, and they retained their ability to catalyze the formation of superoxide radicals to inhibit bacterial attachment to a surface [ 17 , 18 , 19 , 20 , 21 ]. The present study looks at the ability of an organo-selenium bandage to not only block the ability of both P. aeruginosa and S. aureus to form a biofilm on the bandage material, but also to inhibit biofilm formation in the underlying wound.…”
Section: Introductionmentioning
confidence: 99%